Language, Identity and Conflict: Examining Collective Identity through the Labels of the Palestinians in Israel. Issue 2 (November 2016) - Amara, Muhammad
Abstract : This article argues that the identity labels attached to the Palestinians in Israel resulted from a reciprocal interchange of ideas between the Israeli political establishment and the Palestinians themselves, as part of the struggle over identity between the two parties. Each side chose identity labeling criteria that fit its narrative. This shows that such labels are not mere terms but rather serve through their historical evolution and political context to reflect the struggle for collective identity by Palestinian citizens among themselves as well as with the Zionist establishment of Israel, and highlights their symbolic significance. The main question which this paper attempts to answer is how the collective identity of the Palestinian citizens of Israel was shaped and determined within the Israeli context.